Identifying the Impact of Shoreline Change on Land Use in Bedono Village with Google Earth - Nagara, Rakyan Paksi; Wibowo, Adi (Journal of Community Based Environmental Engineering and Management, 2024)
Sloping coastal areas pose a threat to environmental degradation. Previous data and research show that the north coast of Java Island is a sensitive area to abrasion that was exacerbated by sea level rise and land subsidence, one of which occurs in Bedono Village, Demak Regency. Bedono Village is the village that has lost the most land. Based on the latest administrative boundary data, Bedono Village has been divided into three pockets surrounded by sea areas. This study aims to determine the spatial-temporal impacts of shoreline changes on land use in Bedono Village using Google Earth data. In the last two decades, there has been a significant change in the coastline and its impact on land use change. Residential areas continue to decrease in size, reaching 16.38 ha. Ponds, as the most dominating area in 2003, also continued to decrease in area by 127.27 ha or 100% of the initial area. The loss of this land use was replaced by the inundation of sea water that continued encroaching into the land area. A total of 197 residential building units were lost, or an average of 788 people were affected. This study concluded the severe facts and impacts of shoreline change that must be addressed to reduce potential losses.